VALOR NUTRICIONAL DE LA ALGARROBA (Prosopis pallida) EN LA ALIMENTACIÓN DEL CABALLO - Peñaloza A., Fernando (2002)
The present research was carried out to estimate the nutritional value of carob bean (Prosopis pallida) in horses. Four rations with increasing carob bean levels (0; 20: 46.7 y 66.7%) in a base-diet of barley and lucerne hay were evaluated. Four Anglo-Argentinien crossbred geldings were fed the four rations using a simple overchange model with an arrangement of the 4 x 4 Latin Square. A feeding-test consisting of lucerne hay alone was previously done, aiming at obtaining digestibility of carob bean by difference in percentage with the treatment containing 66.77% carob bean. Digestibility of both dry and organic matter was 62.1% and 61.6%, respectively. The increase of carob bean’s content in rations reduced digestibility in most nutritional fractions of feeding rations, with the exception of ethereal extract. Reduction followed a linear, significant pattern (P<0.05) for organic matter, nitrogen-free extract, neutral detergent fibre and acid detergent fibre